Current issues of mental health of military officers of the sector of security and defense of Ukraine - Shemchuk Оксана; Vasiukova Наталія; Dzeruzhynska Наталія; Shemchuk Вадим (Psychosomatic Medicine and General Practice, 2023)
Abstract. The article examines the problems faced by military and medical psychologists, specialists in moral and psychological support, chaplains who work directly with servicemen in military units and units. Special attention is paid to the effective system of training the specified categories of servicemen and workers in the direction of providing qualified medical and psychological assistance to servicemen and civilians who have psychological and psychiatric problems that arose during the suprathreshold action of stressors related to the war. In the course of a theoretical analysis of the historical evolution of the methods of providing psychological assistance to military and civilian contingents in wars and local conflicts of the past century and the present, and taking into account the results obtained, problematic issues of prevention of occurrence and treatment of diseases related to the health of servicemen of the sector were identified and characterized security and defense of Ukraine with the help of reforming military education in the direction of fundamentally new approaches to the training of military personnel who work directly with this category of servicemen, we will characterize the definition of "mental health" in the "health" system in general.The investigated issue is extremely important in the system of moral, psychological and medical support, the quality and timeliness of the provision of psychological and psychiatric services aimed at maintaining the mental health of military personnel at an appropriate level depends not only on their high-quality performance of assigned tasks, but also to a large extent on prevention suicidal cases and other severe psychiatric pathology, which causes military personnel to be unfit for work.